HUBUNGAN PERSEPSI PASIEN TERHADAP PENERAPAN EMPAT PILAR PADA PENANGANAN DIABETES MELITUS DI PUSKESMAS SIMPANG IV SIPIN - Selzi Dhea Astikayuni; Dini Rudini; Putri Irwanti Sari; Nurhusna; Andi Subandi (Forind Press, 2026)
Diabetes mellitus is a non-communicable disease that continues to increase and requires long-term management through the implementation of four pillars of care: education, medical nutrition therapy, physical activity, and pharmacological therapy. The successful implementation of these pillars is influenced not only by clinical factors but also by patients’ perceptions of the disease and its management. This study aimed to determine the relationship between patients’ perceptions and the implementation of the four pillars in the management of diabetes mellitus at the Simpang IV Sipin Community Health Center. This was a quantitative study with a correlational analytic design using a cross-sectional approach. The population consisted of 250 patients, with 78 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using the Spearman Rank test. The results showed that most respondents had good perceptions (51.3%) and good implementation of the four pillars (70.5%). A positive and significant relationship was found between patients’ perceptions and the implementation of the four pillars (r = 0.607; p = 0.000). Healthcare providers are recommended to enhance perception-based education to support optimal diabetes management.